The role of the East Java innovation hub in fostering good local governance. - Setiadi, Redhi (Governance briefs., 2019)
In 2015, an innovation hub was established in East Java to promote public service innovations in 38 district and city governments of the province. Through online and offline mechanisms, it brought together local government, civil society organizations, the private sector, donors, and other stakeholders to share knowledge and solutions. The brief explains how the hub operates and looks at some of its key successes. It also assesses the challenges and opportunities facing such hubs and makes recommendations to strengthen their effectiveness.